2009
DOI: 10.1080/08927010902913187
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated/siloxane copolymer blends for fouling release: chemical characterisation and biological evaluation with algae and barnacles

Abstract: Fouling-release coatings were prepared from blends of a fluorinated/siloxane copolymer with a poly(dimethyl siloxane) (PDMS) matrix in order to couple the low modulus character of PDMS with the low surface tension typical for fluorinated polymers. The content of the surface-active copolymer was varied in the blend over a broad range (0.15-10 wt % with respect to PDMS). X-ray photoelectron spectroscopy depth profiling analyses were performed on the coatings to establish the distribution of specific chemical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 56 publications
3
75
0
Order By: Relevance
“…[9] For example, we have very recently shown that fluorinated/siloxane copolymers and their blends with PDMS have excellent release properties against marine biofouling organisms, such as barnacle, Balanus amphitrite, cyprids, and young plants of the macroalga Ulva linza. [10] Novel random copolymers were synthesized by free-radical polymerization of a bicycloacrylate monomer carrying a fluorocarbon chain side group (BAF10) with a methacrylate monomer having a polysiloxane side graft (SiMA). The copolymers with higher contents of BAF10 gave rise to a well-ordered smectic bilayer mesophase.…”
Section: Introductionmentioning
confidence: 99%
“…[9] For example, we have very recently shown that fluorinated/siloxane copolymers and their blends with PDMS have excellent release properties against marine biofouling organisms, such as barnacle, Balanus amphitrite, cyprids, and young plants of the macroalga Ulva linza. [10] Novel random copolymers were synthesized by free-radical polymerization of a bicycloacrylate monomer carrying a fluorocarbon chain side group (BAF10) with a methacrylate monomer having a polysiloxane side graft (SiMA). The copolymers with higher contents of BAF10 gave rise to a well-ordered smectic bilayer mesophase.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the ability of isopropanol to discriminate more selectively between fluorine-rich and silicon-rich surface phases than do other wetting liquids that are normally used to measure y of polymer films. Densely fluorinated surfaces present large y IP (4*608), whereas PDMS populated surfaces are highly or totally wetted by this solvent (y IP 5*258) (Marabotti et al 2009;Martinelli et al 2009a). However, the competition between the two low surface energy constituent blocks of the block copolymers would result in comparatively low y IP .…”
Section: Wetting Behaviour and Surface Tensionmentioning
confidence: 99%
“…Fluorosilicones showed excellent release of the green seaweed, Ulva, and barnacles compared to the control silicone (Marabotti et al 2009), although the release of diatoms was not improved (unpublished data). In the last few years, a widely researched strategy to improve the FR properties of polymers consists of combining hydrophobic, low surface energy fluorinated moieties with hydrophilic poly(ethylene glycol) (PEG) segments in the same coating (Gudipati et al 2005;Krishnan et al 2008;Martinelli et al 2008;Grozea and Walker 2009;Park et al 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the dilution effects are offset by the chemical incompatibility between the dispersed fluorinated block copolymer and the SEBS matrix, which on the other hand enhances the selfassembly process of the fluorinated chains at the outer surface of the films. The phenomenon of surface segregation is known for a variety of fluorinated polymers, [21,22] polymer blends and networks [16,23,24] and is here pursued as a tool to construct low surface energy, nonwetting polymer coatings.…”
Section: Wetting Behavior and Surface Energymentioning
confidence: 99%